DEVELOPMENT OF METAPLORE “META THE EXPLORER” LEARNING MEDIA BASED ON AUGMENTED REALITY ON INSECT METAMORPHOSIS - Rosmiati, Cici; Andriana, Encep; Yuliana, Rina (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
This research aims to produce a product in the form of augmented reality-based learning media on insect metamorphosis that is suitable for use as a supporting tool in learning activities for 4th grade students. Research and Development is the type of research used, adapted using the ADDIE model. The subjects of this research were the 20 4th grade students at SDN Serang 7. Data collection in this research used questionnaires as responses from students to the Metaplore AR-based learning media. The learning media was declared valid based on the assessment of two media experts, two content experts, and two language experts, with validity percentages of 83.1% (very good), 77.8% (good), and 78.9% (good), respectively. The media was rated by students with a percentage of 89.2% as very good. The results indicate that the Metaplore Augmented Reality-based learning media suits 4th grade students at SDN Serang 7.